1997
DOI: 10.1074/jbc.272.9.5792
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Mitogen-activated Protein Kinase via the A2A-Adenosine Receptor in Primary Human Endothelial Cells

Abstract: When released into or formed in the extracellular space, adenosine acts as an autacoid via interaction with four types of G protein 1 -coupled receptors, termed A 1 -, A 2A -, A 2B -, and A 3 -adenosine receptor. These receptors are encoded by distinct genes and can be differentiated based on their affinities for adenosine analogues and methylxanthine antagonists (1, 2). In addition, the receptors can be classified based on their mechanism of signal transduction; A 1 -and A 3 -adenosine receptors interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
111
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 48 publications
(36 reference statements)
9
111
1
2
Order By: Relevance
“…These receptors are classified according to use of pertussis toxin-sensitive pathways (A 1 and A 3 ) or adenylate cyclase activation pathways (A 2A and A 2B ) (5). Endothelial cells of many origins express constitutive adenosine receptors (5), primarily of the A 2A and A 2B subtypes (27)(28)(29)(30). The present studies define a transcriptional pathway mediated by adenosine receptor activation, including but not limited to CD73.…”
Section: Discussionmentioning
confidence: 68%
“…These receptors are classified according to use of pertussis toxin-sensitive pathways (A 1 and A 3 ) or adenylate cyclase activation pathways (A 2A and A 2B ) (5). Endothelial cells of many origins express constitutive adenosine receptors (5), primarily of the A 2A and A 2B subtypes (27)(28)(29)(30). The present studies define a transcriptional pathway mediated by adenosine receptor activation, including but not limited to CD73.…”
Section: Discussionmentioning
confidence: 68%
“…The activation of adenylyl cyclase induces an increase in cAMP levels, which in turn activates PKA (14,19,50,51). In addition, a previous report indicated that down-regulation of G s␣ abolishes ISO-induced ERK activation in human endothelial cells (25), suggesting that G s␣ is required for activation of ERKs by ␤-AR. Our previous (7) and present studies also showed that ISO activates ERKs through cAMP/PKA in cardiac myocytes, supporting that G s protein plays an essential role in the activation of ERKs.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, in some cell types such as PC12 cells, Swiss-3T3 cells, and S49 mouse lymphoma cells, cAMP activates ERKs and potentiates the effects of growth factors on differentiation and gene expression (20 -24). In human endothelial cells, down-regulation of the ␣ subunit of G s (G s␣ ) abolishes ␤-AR-mediated ERK activation by ISO (25), suggesting that G s␣ -dependent cAMP elevation and PKA activation are responsible for the activation of ERKs. We and others have also demonstrated that ␤-AR agonists including ISO significantly activate ERKs and increase protein synthesis through cAMP/PKA in cardiac myocytes (6,7).…”
mentioning
confidence: 99%
“…8 The apparent discrepancy between these findings and a role of adenosine A 2A receptors can be explained considering the possible coupling of (MEK1) or pertussis toxin-inhibitable G i proteins. [26][27][28] It is noteworthy that stimulation of adenosine A 2A -receptor protects liver sinusoidal endothelial cells against reperfusion injury 9 and reduces TNF-␣ release by lipopolysaccharide-stimulated Kupffer cells. 29 However, in both these cell types a cyclic-AMP dependent pathway appears to be coupled with the stimulation of adenosine A 2A -receptors.…”
Section: Discussionmentioning
confidence: 99%